A framework of privacy shield in organizational information systems - Skinner, Geoffrey; Han, Song; Chang, Elizabeth (IEEE, 2005)
Preserving Privacy and the protection of personally identifiable information (PII) have been of increasing interest over the last few years. Many privacy advocates, and a significant portion of the general public, feared that the new initiatives used in an attempt to fight terrorism, would have a serious impact on an individual?s right and ability to protect their privacy. This paper proposes a new framework for Preserving Privacy for individuals along with the protection of personally identifiable information. We have termed it Privacy Shield. Through the application of anonymity and privacy principles in design, the privacy protecting separation of data, the use of public key infrastructure, and the application of our Information System Hippocratic Policies, we provide a framework of privacy shield to protect an information system user?s personal data.